Shilling & Smith acquisition of Xteria Inc. : data center technology leasing - Jeffery, Mark, 1965-; Shield, Cassidy; Conley, Mike, active 2006; Ekici, H. Nevin (London : Kellogg School of Management, 2006)
The Shilling & Smith case examines how to evaluate different lease options when acquiring data center information technology (IT) infrastructure. Specifically, the case addresses software versus hardware leasing, various lease terms, and choosing between different lease structures depending on the strategy and needs of the company. A secondary objective of the case is to teach students the important components of IT infrastructure.
Originally published in Jeffery, M., Shield, C., Conley, M., & Ekici, H. N. (2006). Shilling & Smith acquisition of Xteria Inc.: Data center technology leasing. 5-404-7731. Evanston, IL: Kellogg School of Management at Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Baker Schilling Smith Wealth Strategies; Computer leases -- Evaluation; Information technology -- Management -- Case studies